Transgenic mice with expression of elevated levels of copper-zinc superoxide dismutase in the lungs are resistant to pulmonary oxygen toxicity. - White, C W (1991)
To test the hypothesis that increases in lung superoxide dismutase can cause tolerance to pulmonary oxygen toxicity, we studied transgenic mice which constitutively express elevated levels of the human copper-zinc SOD (CuZnSOD). Upon exposure to hyperoxia (greater than 99% O2, 630 torr) the transgenic CuZnSOD mice showed increased survival, decreased morphologic evidence of lung damage such as edema and hyaline membrane formation, and reduction in the number of lung neutrophils. During continuous exposure to oxygen, both control and transgenic animals who successfully adapted to hyperoxia showed increased activity of lung antioxidant enzymes such as glutathione peroxidase (GPX), glutathione reductase (GR), and glucose-6-phosphate dehydrogenase (G6PD), whereas superoxide dismutase activity remained unchanged. The results show that expression of elevated levels of CuZnSOD decreases pulmonary oxygen toxicity and associated histologic damage and mortality.